IPGRI thematic report 2000-2001 - International Plant Genetic Resources Institute (2003)
IPGRI's programme is complex, with many related activities going on in different parts of the world, in different projects, and on different crops. This report brings together some of these activities under selected 'themes'. Our aim is to give the reader a clearer picture of how aspects of IPGRI's diverse programme link and build more generalized understanding of issues in the conservation and use of plant genetic resources. The six stories focus on issues as diverse as cryopreservation and in vitro conservation of 'problem' crops, in situ and on-farm conservation and the policy environment that shapes the world of PGR conservation efforts. Each article provides an overview of work in the area by IPGRI and its partners: boxes, reading lists and names of contact persons provide opportunities for the reader to explore the topics further. This volume also provides brief descriptions of achievements of all the individual activities of the IPGRI programme, and is thus a one-stop reference to the institute's work.The work presented here is not that of IPGRI alone, but of our many partners around the world. We wish to take this opportunity to acknowledge the contribution of our many colleagues and partners around the world: their dedication to the goal of conserving and using plant genetic resources in support of human development inspires our efforts. We also wish to acknowledge our gratitude to our many supporters, especially the donors who invest in our efforts. Together, we are building a food-secure future on a solid foundation of plant genetic resources conservation and use.